2017
DOI: 10.17265/2162-5263/2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Applied Biofloc Technology for Target Species in the Mekong Delta in Vietnam: A Review

Abstract: BFT (Biofloc Technology) has been currently applied in Cantho University to a number of targeted species from fresh-to marine and saline water species in the Mekong Delta, e.g. striped catfish (Pangasianodon hypophthalmus), white leg shrimp (Litopenaeus vannamei), tiger shrimp (Penaeus monodon) and Artemia Vinhchau strain (Artemia franciscana) for both in the lab-scales or production scales. The best growth and survival rate of striped catfish was obtained in 6‰. For white leg shrimp, the results indicated: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The increasingly popular approach to managing ponds using biofloc systems in aquaculture is widely discussed 37,68,69 . This involves providing a nutritious food source that promotes higher productivity or higher nutrient in an integrated aquaculture system.…”
Section: Direct and Indirect Use Of Agricultural Waste In Artemia Pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…The increasingly popular approach to managing ponds using biofloc systems in aquaculture is widely discussed 37,68,69 . This involves providing a nutritious food source that promotes higher productivity or higher nutrient in an integrated aquaculture system.…”
Section: Direct and Indirect Use Of Agricultural Waste In Artemia Pro...mentioning
confidence: 99%
“…67 The increasingly popular approach to managing ponds using biofloc systems in aquaculture is widely discussed. 37,68,69 This involves providing a nutritious food source that promotes higher productivity or higher nutrient in an integrated aquaculture system. These studies followed after it was reported that bacteria could be used as a nutrient source for Artemia to compensate for suboptimal algae supply when molasses supplementation resulted in much lower total Artemia biomass compared to significant improvement when beneficial bacteria were combined with molasses.…”
Section: Direct Addition Of Waste As Fertilisermentioning
confidence: 99%